Vazões ecológicas na bacia hidrográfica do Rio Piquiri - Herther, Cintia Caroline Krebs (2016)
The instream flows are also known as environmental flow, residual flow, remaining flow among other designations that correspond to the amount of water that must remain into river bed to meet survival and preservation needs of the aquatic ecosystem. Thus, this study aimed at carrying out a comparative analysis among the different hydrological methods in order to obtain the water flow such as: method of water flow base, method of Q90 and Q95 duration curve, method of minimum annual flows of 7 days, and the method of the average minimum flow of 7 days with 10-year reoccurrence period (Q7,10), in Piquiri river basin. There was a comparison among those methods as well as for each station. The largest estimates of flow rates among the methods were obtained with the base water flow method and the lowest values were recorded by the Q7,10 method. In most stations, the method of base water flow was the highest, except at the station (64776100), whose Q90 flow value was superior as well as at the station (64785000), whose highest value of flow was recorded in the annual average of minimum stream flow of seven days. For all stations, the Q7,10 method showed the lowest values of environmental flow, which is a restrictive estimate when compared to the grantable maximum limit in Paraná state.